Verteporfin photodynamic therapy combined with intravitreal triamcinolone for choroidal neovascularization due to angioid streaks - Alfredo Pece (Dove Medical Press, 2010)
Alfredo Pece1, Gaetano Russo2, Federico Ricci3, Vincenzo Isola1, Ugo Introini4, Giuseppe Querques51Department of Ophthalmology, Melegnano Hospital, Milan, Italy; 2Fondazione Evangelica Betania, Napoli, Italy; 3University of Tor Vergata, Rome, Italy; 5University, Paris XII, France; 4San Raffaele University Hospital, Milan, ItalyPurpose: To report the visual outcome of photodynamic therapy (PDT) combined with intravitreal triamcinolone acetonide (IVTA) for choroidal neovascularization (CNV) secondary to angioid streaks (AS).Methods: Five eyes of five consecutive patients (mean age 45 ± 10 years) with CNV secondary to AS were treated by combination of PDT and IVTA. TA (4 mg/0.1 mL) was injected 7 days before PDT.Results: All patients completed the 12-month follow-up. CNV was subfoveal in three cases and extrafoveal in two. Median best-corrected visual acuity (BCVA) was 0.3 LogMAR (70 letters) at baseline (range 1.3–0.1), and 0.5 LogMAR (60 letters) at the final examination (range 1.0–0.1). At 12 months, one patient had severe visual deterioration, with a loss of seven lines of VA; Two patients lost up to three lines. One patient had no change in BCVA and the fifth gained nine lines of VA. Two patients received one further combination of PDT and IVTA after the first combination treatment. All eyes showed the CNV closure at the 12-month follow-up visit.Conclusions: Combination of PDT and IVTA may reduce the need for retreatment and could be potentially useful for preserving vision in some patients with CNV due to AS. Keywords: ocular corticosteroids